Updated guidance on the management of COVID-19: from an American Thoracic Society/European Respiratory Society coordinated International Task Force (29 July 2020). (5th October 2020) - Bai, Chunxue; Chotirmall, Sanjay H.; Rello, Jordi; Alba, George A.; Ginns, Leo C.; Krishnan, Jerry A.; Rogers, Robert; Bendstrup, Elisabeth; Burgel, Pierre-Regis; Chalmers, James D.; Chua, Abigail; Crothers, Kristina A.; et al.
Background: Coronavirus disease 2019 (COVID-19) is a disease caused by severe acute respiratory syndrome-coronavirus-2. Consensus suggestions can standardise care, thereby improving outcomes and facilitating future research. Methods: An International Task Force was composed and agreement regarding courses of action was measured using the Convergence of Opinion on Recommendations and Evidence (CORE) process. 70% agreement was necessary to make a consensus suggestion. Results: The Task Force made consensus suggestions to treat patients with acute COVID-19 pneumonia with remdesivir and dexamethasone but suggested against hydroxychloroquine except in the context of a clinical trial; these are revisions of prior suggestions resulting from the interim publication of several randomised trials. It also suggested that COVID-19 patients with a venous thromboembolic event be treated with therapeutic anticoagulant therapy for 3 months. The Task Force was unable to reach sufficient agreement to yield consensus suggestions for the post-hospital care of COVID-19 survivors. The Task Force fell one vote shy of suggesting routine screening for depression, anxiety and post-traumatic stress disorder. Conclusions: The Task Force addressed questions related to pharmacotherapy in patients with COVID-19 and the post-hospital care of survivors, yielding several consensus suggestions. Management options for which there is insufficient agreement to formulate a suggestion represent research priorities. For patients with acute COVID-19 pneumonia who require oxygen support, the International Task Force made suggestions for remdesivir and dexamethasone, but against hydroxychloroquine. Post-discharge management of COVID-19 survivors is a research priority. https://bit.ly/32B96uI